Pengembangan Multimedia Pembelajaran Inquiry Berbasis Kimia Komputasi untuk Peningkatan Hasil Belajar Siswa Pada Materi Laju Reaksi - Sinaga, Juanda; Gideon Rajagukguk; Asep Wahyu Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and test the feasibility and effectiveness of computational chemistry-based inquiry learning media on Reaction Rate material at SMAN 14 Medan. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 29 grade XI students. The product was validated by media experts and material experts, with feasibility results of 92.77% and 93.64% in the very feasible category. Student responses showed an average percentage of 86% in the very good category, indicating high acceptance and interest in the media. Effectiveness tests through pretest and posttest showed an increase in the average value from 45.86 to 85.51, and an N-Gain value of 70.16% (high category). The results of the study prove that the developed learning media is feasible, practical, and effective in improving students' chemistry learning outcomes on Reaction Rate material